A Short Review of Influencing Factors of Islamic Architecture in Aleppo, Syria - Noaime, E.; Osman, A.; Said, M. A.; Abdullah, G.; Touahmia, M.; Nasser, Y.; Salah, K.; Hassan, M. (Engineering, Technology & Applied Science Research, 2020)
This research aims to examine Aleppo’s distinctive architectural design profiles, most precisely those of residential buildings, and to highlight factors that indicate how the Islamic culture influenced the architectural structure in the pre-civil war era. Descriptive research, observation, and documentation of architectural elements that determine the general characteristics of housing in the city of Aleppo were used. The study focused on Wakil and Zamriah houses as case studies because of their accessibility and excellent exemplary style. The current study sheds light on the history of Aleppo’s urban development and its influence by the Islamic civilization during the late Ottoman era up to the Syrian civil war in 2011. It is shown how Islamic civilization influenced Aleppo’s residential buildings in terms of simplicity, respect for human scale, equality, and privacy.